2021
DOI: 10.3390/cells10051143
|View full text |Cite
|
Sign up to set email alerts
|

Pericoronary Adipose Tissue Attenuation Is Associated with High-Risk Plaque and Subsequent Acute Coronary Syndrome in Patients with Stable Coronary Artery Disease

Abstract: Background: High-risk plaques (HRP) detected on coronary computed tomography angiography (CTA) confer an increased risk of acute coronary syndrome (ACS). Pericoronary adipose tissue attenuation (PCAT) is a novel biomarker of coronary inflammation. This study aimed to evaluate the association of PCAT with HRP and subsequent ACS development in patients with stable coronary artery disease (CAD). Methods: Patients with stable CAD who underwent coronary CTA from 2011 to 2016 and had available outcome data were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 34 publications
(66 reference statements)
1
23
1
Order By: Relevance
“…It may interact with endothelial damage caused by high LDL-C, CysC, and DD and jointly promote the process of CHD [16,17]. erefore, regular detection of serum LDL-C, CysC, and D-D levels in patients with hypertension plays a signi cant role in evaluating the degree of target organ damage in cases with essential hypertension and the treatment and prognosis of hypertension [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may interact with endothelial damage caused by high LDL-C, CysC, and DD and jointly promote the process of CHD [16,17]. erefore, regular detection of serum LDL-C, CysC, and D-D levels in patients with hypertension plays a signi cant role in evaluating the degree of target organ damage in cases with essential hypertension and the treatment and prognosis of hypertension [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…It may interact with endothelial damage caused by high LDL-C, CysC, and DD and jointly promote the process of CHD [ 16 , 17 ]. Therefore, regular detection of serum LDL-C, CysC, and D-D levels in patients with hypertension plays a significant role in evaluating the degree of target organ damage in cases with essential hypertension and the treatment and prognosis of hypertension [ 18 , 19 ]. In addition, this study found that the AUC of the combination of LDL-C, CysC, and D-D for the diagnosis of CHD was 0.868, and the sensitivity and specificity were 88.89% and 73.33%, respectively, suggesting that the combination of the above three indicators has good diagnostic performance in CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies mainly focused on the RCA to represent overall pericoronary attenuation, without evaluating potential differences between the RCA, LAD and LCx [6,15,[24][25][26]. The proximal RCA is characterized by the absence of confounding non-fatty structures such as side branches, coronary veins, or myocardium, and also by the highest volume of surrounding adipose tissue [4,27].…”
Section: Differences In Pcat Attenuation Among the Different Coronary...mentioning
confidence: 99%
“…Right coronary artery peri-coronary adipose tissue attenuation is associated with CV risk factors and significant coronary stenoses [ 83 ]. Epicardial adipose tissue secretes adipocytokines, leading to a pro-inflammatory state and progression of atherosclerotic disease [ 21 , 84 , 85 ]. Therefore, the presence of peri-coronary adipose tissue especially around the right coronary artery is suggested as a promising imaging biomarker to allow non-invasive assessment of coronary inflammation.…”
Section: High-risk Plaque Featuresmentioning
confidence: 99%